(untitled) (Canadian Medical Education Journal, 2022)
Purpose: Due to the coronavirus disease 2019 pandemic, all Canadian Resident Matching Service interviews for internal medicine subspecialty programs were conducted virtually for the first time. This study explored the perceptions and experiences of internal medicine residents, subspecialty medicine program directors, and interviewers during virtual interviews. Methods: We invited all Canadian third-year IM residents, subspecialty program directors, and interviewers who participated in the 2020 medical subspecialty medicine interviews to complete a branching survey with a section for residents and one for program directors and interviewers. We distributed the anonymous survey after the submission of the rank order lists, to not affect residency match outcomes. Qualitative data were open-coded thematically and quantitative data were cleaned and then statistically analyzed using descriptive statistics and Analysis of Variance tests. Results: 62 residents, 59 program directors, and 113 interviewers responded to the survey with representation from almost all Canadian medical faculties and medical subspecialties. Strengths of virtual interviews included reduced cost, stress, pandemic infection risk, and carbon footprint. Weaknesses of virtual interviews included decreased ability to connect personally and informally, and inability to tour medical facilities and cities. A majority of both resident respondents (59.6%) and program directors/interviewer respondents (54.6%) supported conducting interviews virtually in the future. Conclusions: This study showed that the majority of both sampled residents and program directors/interviewers would prefer to conduct medicine subspecialty match interviews virtually in the future, and provides suggestions on how to improve the virtual interviews for the next iteration.